Sustainable Development Goals (SDGs), Digital Education and Digital School - Agung Prajuhana; Eri Sarimanah; Tutus Rully; Muhammad Ikhsan Setiawan; Agus Sukoco; Sugeng Sugeng; Abdul Talib Bon (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Promoting digital education, the SDG Fund is convening partnerships between UN Agencies, governments and the telecommunications industry to better use information technologies to advance SDG4. Affordable, reliable and context-sensitive digital education, can promote equal opportunities for girls and boys and reduce inequalities by ensuring every child has access to high quality content. Digital education technologies improves fundamental skills such as collaboration, problem solving and global awareness. Design/methodology/approach: Sustainable Development Goals (SDGs), Digital Education Documents by funding sponsor, Compare the document counts for up to 15 funding sponsors, first European Commission, followed by National Natural Science Foundation of China, and Horizon 2020 Framework Programme. Documents by affiliation, Compare the document counts for up to 15 affiliations, first University College London, followed by University of Oxford and University of Washington. Subject area Documents, first Social Sciences, followed by Environmental Science and Computer Science. Documents by country or territory, Compare the document counts for up to 15 countries/territories, first United States, followed by United Kingdom and Spain. In ASIA, first India and China. In ASEAN, first Malaysia, followed by Indonesia, Singapore, Thailand, Philippines, and Viet Nam. From Indonesia, Documents by funding sponsor, Compare the document counts for up to 15 funding sponsors, first Direktorat Jenderal Pendidikan Tinggi, followed by Universitas Airlangga, Universitas Indonesia and Universitas Padjadjaran. Documents by affiliation, Compare the document counts for up to 15 affiliations, first Universitas Indonesia and Universitas Sebelas Maret. Sustainable Development Goals (SDGs), Digital Education, Documents by funding sponsor, Compare the document counts for up to 15 funding sponsors, first National Natural Science Foundation of China, European Commission, and Horizon 2020 Framework Programme. Findings: Documents per year by source, first Sustainability Switzerland journal, Journal Of Cleaner Production, and Remote Sensing journal. Documents by affiliation, Compare the document counts for up to 15 affiliations, first University of Washington, Columbia University, and London School of Hygiene. Documents by country or territory, Compare the document counts for up to 15 countries/territories, first United Kingdom, United States, and Australia, in ASIA, first China, India, and Japan. In ASEAN first Malaysia, Singapore, Thailand, Indonesia, Viet Nam, Philippines, and Cambodia. In Indonesia, Documents by funding sponsor, Compare the document counts for up to 15 funding sponsors, first Binus University, Direktorat Jenderal Pendidikan Tinggi, Lembaga Pengelola Dana Pendidikan, Universitas Airlangga, Universitas Indonesia, Universitas Katolik Parahyangan, and Universitas Sebelas Maret. Documents by affiliation, Compare the document counts for up to 15 affiliations, first Universitas Indonesia and Universitas Sebelas Maret. Universitas Indonesia and Universitas Sebelas Maret are dominant in Indonesia for Sustainable Development Goals (SDGs), Digital Education, Digital Education, research publication. Paper type: Research paper